A compact leaky‐wave antenna using a planar spoof surface plasmon polariton structure. Issue 5 (14th January 2019) - Hao, Zhang‐Cheng; Zhang, Jianxiong; Zhao, Lei
Abstract: This article presents and validates a leaky‐wave antenna by using the spoof surface plasmon polariton (SSPP) technique. By properly designing the proposed SSPP unit, the SSPP wave can be switched between the confinement and radiation modes. A large radiation efficiency can be achieved by properly designing the modulation depth, which ensures that a compact SSPP leaky‐wave array can be realized by using a small number of SSPP radiation units. To verify the design, a prototype which consists of a SSPP feeding network and a 4 by 4 SSPP radiation units has been fabricated by using a low cost FR‐4 substrate. A good agreement between simulated and measured results has been obtained. The proposed array antenna shows the promising capability of the SSPP technique for leaky‐wave antenna applications.